2006
DOI: 10.1080/08860220600925602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occult Hepatitis B and Hepatitis C Virus Infections in Turkish Hemodialysis Patients

Abstract: Both occult and non-occult forms of HCV infection are more prevalent than HBV infection in hemodialysis patients. Especially the patients with isolated anti-HBc positivity should be tested for probable occult hepatitis B infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 40 publications
5
63
0
1
Order By: Relevance
“…In another study conducted in Turkey, 13% of recruited hemodialysis patients were HBsAg positive, 20% were HCV positive, and 4% showed HBV and HCV coinfections (4). The prevalence of HBV and HCV has been studied previously in Iraq in different groups, such as blood donors, healthcare workers, and thalassaemia patients (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Turkey, 13% of recruited hemodialysis patients were HBsAg positive, 20% were HCV positive, and 4% showed HBV and HCV coinfections (4). The prevalence of HBV and HCV has been studied previously in Iraq in different groups, such as blood donors, healthcare workers, and thalassaemia patients (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In general, North Africa and the Middle East were cited as high prevalence areas, both in the general population and in HD patients, by the WHO in 1999 [9] . Previous studies from the region have reported a prevalence of anti-HCV antibodies in HD patients of 50% in Saudi Arabia in 2000 [10] , 19.1% in Tunisia in 1994 [11] , 20.2% in Turkey in 2006 [12] and 34.6% in Jordan in 2007 [13] . Concerning the prevalence of HBV, Abourached et al [5] reported on 2007 a prevalence of 2.62% (0%-6.5%) of HBsAg in 17 HD centers in Lebanon, our study showed a decrease of the prevalence to 1.6%, ranging from 1.4% in Nabatieh and Bekaa, to 2.4% in the North.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence (per patient-year) = [(Total number of acquired infection)/(Total patient|month)]/ 12 We did the statistical analysis separately for HBV and HCV.…”
Section: Incidence Analysismentioning
confidence: 99%
“…12 This criteria has been modified by some workers to define occult HCV infection as anti-HCV negative and HCV-RNA positive by PCR while evaluating the prevalence of HCV infection in patients on dialysis. [9][10][11] We used the same criteria and performed quantitative HCV-RNA assay by real time PCR to assess the prevalence of occult HCV infection in RT patients on our follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also defined occult HCV infection as anti-HCV negative and HCV-RNA positive by polymerase chain reaction (PCR) while evaluating the prevalence of HCV infection in patients on dialysis. [9][10][11] But there is a lack of data on the prevalence of occult HCV infection in RT patients. We studied the prevalence of occult HCV infection in RT recipients on our follow-up and analysed the factors that influence this prevalence.…”
Section: Introductionmentioning
confidence: 99%